Society Islands beach bum black flies (Diptera: Simuliidae) - Craig, Douglas A.; Evenhuis, Neal L. (Zootaxa, 2017)
Aspects of the body of work on the Central and Western Pacific black fly Simulium (Inseliellum) are briefly reviewed. Female adults collected from beaches in Tahiti and Raiatea are described as Simulium (Inseliellum) littopyga n. sp., Simulium (Inseliellum) littosocius n. sp. and Simulium (Inseliellum) littosodalis n. sp.. Immature stages of the three species are not associated.